Development of FRET-based cap-snatching endonuclease assay - Jeeva Subbiah; Austin Royster; Sheema Mir; Mohammad Mir (Microbiology Spectrum)
ABSTRACT The order Bunyavirales consists of over 300 species of segmented, negative-strand RNA viruses. These viruses have a tri-segmented genome (S, M, and L segments) that encodes the nucleocapsid protein (N protein), glycoprotein precursor, and RNA-dependent RNA polymerase (RdRp), respectively. The RdRp is a large protein (~420 kDa) responsible for synthesizing viral mRNA and replicating the viral genome. Bunyaviruses initiate transcription of viral mRNA through a unique cap-snatching mechanism. During this process, the N-terminal endonuclease domain of the RdRp cleaves host cell mRNA at the 5′ terminus and uses the resulting capped mRNA fragment as a primer. This endonuclease domain exhibits a highly conserved structural architecture and is essential for establishing viral infection in host cells. Therefore, the N-terminal endonuclease domain represents a promising target for therapeutic intervention against Bunyaviruses, particularly at the early stages of the virus replication cycle. In this study, we developed a highly sensitive fluorescence resonance energy transfer-based in vitro assay to quantitatively examine the activity of the bacterially expressed and purified endonuclease domain of hantavirus RdRp. A 20-nucleotide synthetic RNA, labeled with a 6-FAM fluorophore at the 5′ end and an Iowa Black quencher at the 3′ end, generated a significant dequenched fluorescence signal upon cleavage by the purified endonuclease domain. Kinetic analysis revealed a half-life (t1/2) of approximately 3 min for the reaction, achieving a signal-to-background ratio of approximately 31.IMPORTANCEViruses belonging to the order Bunyavirales, including Hantaviruses, Crimean–Congo hemorrhagic fever virus, Rift Valley fever virus, Severe Fever with Thrombocytopenia Syndrome Virus, and La Crosse encephalitis virus, cause severe human illnesses with mortality rates in certain outbreaks reaching 50%, 10%–40%, 10%–20%, 6%–30%, and 1%, respectively. Currently, there are no Food and Drug Administration-approved vaccines or antiviral therapeutics available for these viruses. The highly efficient and cost-effective fluorescence resonance energy transfer-based in vitro endonuclease assay, having a quantitative fluorescence readout, can be optimized for high-throughput screening of chemical libraries to identify chemical inhibitors for the Bunyavirus cap-snatching endonuclease. The assay will be of critical importance for antiviral drug discovery against numerous negative-strand RNA viruses using cap-snatching mechanism for transcription initiation and replication of the RNA genome.